ArcPy and ArcGIS, geospatial analysis with python : use the ArcPy module to automate the analysis and mapping of geospatial data in ArcGIS - Toms, Silas (Packt Publishing, 2015)
Annotation If you are a GIS student or professional who needs an understanding of how to use ArcPy to reduce repetitive tasks and perform analysis faster, this book is for you. It is also a valuable book for Python programmers who want to understand how to automate geospatial analyses.
Includes index.
Keywords: ArcGIS.; ArcGIS; Geographic information systems.; Graphical user interfaces (Computer systems); Python (Computer program language); elektronické knihy; electronic books